Stress during clinical practicum in medical-surgical ward among UNIMAS nursing students - Lydia, Awang. (UNIMAS, 2009)
The purpose of this descriptive study was to examine the stress intensity among UNIMAS nursing students during their clinical practicum in Medical -Surgical ward. A total of 86 respondents were selected into the study based on purposive sampling. Data was collected through a newly-created questionnaire which is self-fulfilled by the respondents. Descriptive analysis, Mann-Whitney test, Kruskall-Wallis test and Spearman correlation test were used for analysis of the data.The results showed that clinical practicum in Medical Surgical ward was described as being “moderately” stressful. Although there was no significant difference, the descriptive data showed that Year 4 nursing students reported a high level of stress. Female nursing students significantly experienced high level of stress during practicum in Medical-Surgical ward than male nursing students. Besides, the personal-related stressor was rated as the highest stressful stressor and patient-related stressor was rated as the less stressful stressor. There were a lot of stressors encountered by nursing students in clinical area. As a result, it reduces the quality of education in the clinical setting. Hence, an effective and supportive stress intervention program should be plan and develop in helping the students to cope with the stressful situations in the clinical area.